Cytotoxicity Activity and Mechanism of Action of Arborinine, an Acridone Alkaloid from Glycosmis Pentaphylla (RETZ.) DC. - Nurlaili Najmie Binti Mohd Hussain (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2018)
Cancer is one of the deadliest disease and the number of case being increasing over the time. Anticancer treatments are believed to have the ability to induce cell death via apoptosis to prevent the proliferation of cancer cell. Plant-based anticancer is expected to receive a huge public attention due to its potential on cancer therapy and availability of sources. Arborinine which is an acridone alkaloid found exclusively in Rutaceae family has been shown to inhibit proliferation of a wide variety of cancer cell lines. It was isolated from a Malaysian Rutaceae, Glycosmis pentaphylla (Retz.) DC. The present study is aimed to isolate the arborinine and to investigate its cytotoxicity activity with the mechanism of action on human mammary gland adenocarcinoma (MCF-7) cancer cell line. Isolation of arborinine was conducted from the leaves of G. pentaphylla via acid-base extraction and column chromatographic techniques. The structure of arborinine was authenticated by comparing its spectroscopic data with that of published reports. Cytotoxicity activity of arborinine was conducted towards selected cell lines MCF-7, human non-small cell lung carcinoma; A549 and H1299 through 3-(4,5)-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide colorimetric assay (MTT) assay. TdT-dependent dUTP-biotin nick end-labelling (TUNEL) and caspase 3/7 assay were used to investigate the apoptosis mechanism induced. Involvements of cytochrome c and bax protein were further evaluated through western blotting to determine the mechanism of action. The result showed that 0.1295 g (12.16 %) of arborinine was yielded from 1.0653 g of alkaloidal extract. Arborinine showed the most significant inhibitory activity on MCF-7 with IC50 of (10.50 ± 0.58 µM) compared to A549 and H1299 cancer cell lines at all tested concentrations with IC50 of (70.3 ± 1.77 µM) and (75.0 ± 0.29 µM) respectively. Apoptotic nuclei were identified by the presence of dark brown staining and activation of caspase-3 and -7 which further confirmed that the mode of cell death induced by arborinine was via apoptosis. However, the apoptosis triggered by arborinine was not associated with the expression of bax and cytochrome c. The data presented suggest that arborinine can be a potential lead for further investigation in the development of a new anticancer agent against breast cancer.